2004
DOI: 10.1097/01.hco.0000132321.24004.25
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic psychological stress in coronary disease

Abstract: It is suggested that, taken as a whole, evidence for a psychological and social impact on CAD morbidity and mortality is convincing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 63 publications
0
15
0
1
Order By: Relevance
“…Chronic psychosocial stress is a risk factor for the development and progression of cardiovascular disease [CVD; (Hamer, Molloy, & Stamatakis, 2008; Innes, Vincent, & Taylor, 2007; Kopp & Rethelyi, 2004; Ramachandruni, Handberg, & Sheps, 2004)]. Recent research has shown that stress may relate to CVD through its influence on inflammatory processes (Bierhaus, Humpert, & Nawroth, 2006; Steptoe, Hamer, & Chida, 2007).…”
mentioning
confidence: 99%
“…Chronic psychosocial stress is a risk factor for the development and progression of cardiovascular disease [CVD; (Hamer, Molloy, & Stamatakis, 2008; Innes, Vincent, & Taylor, 2007; Kopp & Rethelyi, 2004; Ramachandruni, Handberg, & Sheps, 2004)]. Recent research has shown that stress may relate to CVD through its influence on inflammatory processes (Bierhaus, Humpert, & Nawroth, 2006; Steptoe, Hamer, & Chida, 2007).…”
mentioning
confidence: 99%
“…Moreover, in recent decades interest in the relationship between psychological stress and physical health has been growing rapidly (for reviews, see S. Cohen & Herbert, 1996;Schneiderman, Ironson, & Siegel, 2005). Psychological functioning, in particular exposure to chronic psychological stress and the emotional reactions to same, has been implicated in the development and progression to a wide range of physical diseases including diabetes as well as increases in psychosomatic symptoms such as gastrointestinal problems, upper respiratory tract infections (see Cohen & Herbert, 1996;Pinquart & Sorensen, 2003;Ramachandruni, Handberg, & Sheps, 2004). In older caregivers of patients with schizophrenia (Dyck, Short, & Vitaliano, 1999) and dementia (Lee, Colditz, Berkman, & Kawachi, 2003;Schulz & Beach, 1999) caregiver stress found to predict poorer physical health with higher rates of infection and greater risk of cardiovascular morbidity and mortality being observed.…”
Section: Introductionmentioning
confidence: 99%
“…Various psychosocial stressors, including personality, job stress, and social isolation, have been identified as risk factors for the development of atherosclerosis (13,77,117,146). There is also much evidence to suggest that chronic psychosocial stress is a risk factor specifically for the acceleration of coronary artery disease (41,72,78,110,129,143). Given the proinflammatory activity of the RAS and the evident increase in RAS activity during the stress response, there may be a link between recurrent or chronic stress, recurrent or chronic activation of the RAS, and the development of atherosclerosis.…”
Section: Does Intermittent Acute Stress or Chronic Stress Cause Inflamentioning
confidence: 96%